PENERAPAN MODEL PEMBELAJARAN THINK TALK WRITE (TTW) UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI PENCEMARAN LINGKUNGAN DI KELAS X SMA NEGERI 1 SEKADAU - Marzuki, Marzuki (LPPM Institut Pendidikan Nusantara Global, 2023)
This research aims to determine the improvement in student learning outcomes by using the Think Talk Write (TTW) learning model on environmental pollution material at SMA Negeri 1 Sekadau. There are two variables in this research, namely the application of the Think Talk Write (TTW) learning model as the independent variable and student learning outcomes as the dependent variable. The method in this research is the classroom action research (PTK) method which consists of two cycles, each cycle through four stages, namely planning, action, observation and reflection. Data collection techniques are observation and measurement techniques, with data collection tools namely observation sheets and test questions. The research results showed that in cycle I the average value of student learning outcomes was 68.57 with classical completeness of 71.42% and the average value of cycle II was 77.85% with classical completeness of 92.85%, there was an increase in learning outcomes of 9.28%. The application of the Think Talk Write (TTW) learning model can improve the learning outcomes of class X students at SMA Negeri 1 Sekadau